Pengaruh Struktur Modal dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening (Pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020) - Muhammad Adam Yusuf; Ronny Malavia Mardani; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine how the effect of capital structure and company growth on firm value with profitability as an intervening variable case study on property and real estate companies listed on the Indonesia Stock Exchange for the period 2018 to 2020. The population in this study are all property and real estate companies. registered. on the IDX for the period 2018 to 2020 with a total of 63 companies. The sampling technique used purposive sampling method obtained a sample of data from as many 43 companies. This research data collection uses the method of documentation in the annual report on the IDX. The data analysis technique in this study used path analysis with SPSS 26 software. The results showed that partially the capital structure had a negative significant effect on profitability. The company's growth has a positive significant effect on profitability. Capital structure has positive not significant effect on firm value. Company growth has positive not significant effect on firm value. Profitability has a significant positive effect on firm value. Mediation in this study is completely mediation. Profitability is able to mediate the capital structure of the firm value. Profitability is able to mediate the growth of the company to the value of the company. Keywords: Firm Value, Profitability, Capital Structure, Company's Growth